A slab in the face: Building quality and neighborhood effects - Rainer Schulz; Martin Wersing (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
The quality of newly constructed single-family houses is usually homogeneous in and heterogeneous between neighborhoods. Such quality-clustering will be caused by the variation of natural amenities throughout a suburban area. Clustering will be enforced if the quality of neighboring buildings increases the value of newly constructed ones. To disentangle the natural amenity e ect and the neighborhood e ect, we use data from Berlin and exploit that the endogenous e ect was weakened during the socialist period. Our results show that the exogenous variation caused by buildings constructed during this period still causes lower quality new buildings in the East of the city.
Keywords: R31; D62; C31; 330; housing supply; housing externality; natural experiment; Wohnungsbau; Produktqualität; Nachbarschaftsökonomie; Berlin (Ost)